The adventurer's guide to dragons (and why they keep biting me) - White, Wade Albert (Little, Brown and Company, 2017)
Anne and her best friends Penelope and Hiro are tasked with an unwanted quest that could start a war between the Hierarchy and the dragon clan, and so to avoid disaster and save the world, the three friends must face dragon trials, defeat robots, and circumvent bureaucracy.